Model of Islam Nusantara da'wah based on multiculturalism - Muhyiddin, Ahmad Shofi (Jurnal Ilmu Dakwah, 2023)
Purpose - This study aims to develop a model of Islamic da'wah based on religious and cultural multiculturalism in Indonesia as a response to religious violence.Method - This research was conducted through a literature review (library research) with a philosophical hermeneutic approach in which data related to da'wah scholarship, the term Islam Nusantara, and multiculturalism were analyzed using descriptive-holistic-heuristic elements.Result - The results of the study show that: 1). Islam Nusantara da'wah necessitates the presence of Islam, which is constantly in dialectics with the culture of the people of the Archipelago. In this dialectical process of Islam and culture, it is not uncommon for "Islam Nusantara" to succeed in creating new Islamic symbols that do not exist in the Middle East region. Therefore, several models of da'wa are obtained, including deculturative dialogue da'wah/taghayyur, additive acculturation dialogue da'wah/takammul, considerate acculturation dialogue da'wah/tahammul and inclusive-institutional acculturation dialogue da'wah/tasallum. The da'wah approach used is a structural-formalistic, cultural-naturalistic, and spiritual-intuitive approach. This da'wah approach is applied through dakwah bi al-lisān, dakwah bi al-qalam, and dakwah bi al-ḥāl. 2). The characteristics of Islam Nusantara da'wah based on multiculturalism include: acknowledging and appreciating the uniqueness and diversity of cultures and beliefs, as well as the existence of points of similarity in this diversity, viewing the phenomenon of religion as a culture, and understanding religion in a progressive, dynamic manner and without "sacredism." 3). Da'wah's models in responding to religious violence differ depending on the typologies of causative factors.Implication - This article suggests the development of da'wah scholarship, namely the Islam Nusantara da'wah based on multiculturalism, which allows for corrections, additions, and improvements to developing new knowledge.Originality - This article is a study that shows the formulation of Islam Nusantara da'wah model with a multiculturalism perspective.***Tujuan - Penelitian ini bertujuan untuk mengembangkan model dakwah Islam yang berbasis pada multikulturalitas agama dan budaya di Indonesia sebagai respon terhadap kekerasan beragama.Metode - Penelitian ini dilakukan melalui studi kepustakaan dengan pendekatan hermeneutika filosofis di mana data yang berkaitan dengan keilmuan dakwah, Islam nusantara dan multikulturalisme di analisa dengan menggunakan unsur deskriptif-holistik-heuristik.Hasil - Hasil penelitian menunjukkan bahwa: 1). dakwah Islam Nusantara meniscayakan kehadiran Islam yang terus-menerus berdialektika dengan budaya masyarakat Nusantara. Dalam proses dialektika Islam dan budaya ini, tidak jarang Islam Nusantara berhasil menciptakan simbol-simbol Islam baru yang tidak ada di kawasan Timur Tengah. Oleh karena itu didapatkan beberapa model dakwah, antara lain: dakwah dialog dekulturatif/taghayyur,   dakwah dialog akulturasi aditif/takammul, dakwah dialog akulturasi konsideratif/tahammul dan dakwah dialog akulturasi inklusif-institutif/tasallum. Pendekatan dakwah yang digunakan adalah pendekatan struktural-formalistik, kultural-naturalistik dan spiritual-intuitif. Pendekatan dakwah ini diterapkan melalui metode dakwah bi al-lisān, dakwah bi al-qalam dan dakwah bi al-ḥāl. 2). Karakteristik dakwah Islam Nusantara berbasis multikulturalisme antara lain: mengakui dan menghargai keunikan dan keragaman budaya dan keyakinan, serta adanya titik kesamaan dalam keragaman tersebut, memandang fenomena keberagamaan sebagai kultur, dan memahami agama secara progresiv, dinamis dan tidak ada “pensakralan”.  3). model dakwah dalam merespon fenomena kekerasan beragama berbeda-beda tergantung dari perbedaan tipologi faktor penyebabnya.Implikasi - Artikel ini menyarankan pengembangan keilmuan dakwah, yaitu dakwah Islam Nusantara berbasis multikulturalisme, yang memungkinkan adanya koreksi, penambahan dan penyempurnaan pengembangan ilmu baru.Orisinalitas - Artikel ini merupakan kajian yang menunjukkan formulasi model dakwah Islam Nusantara dengan perspektif multikulturalisme.